2010
DOI: 10.1073/pnas.0912393107
|View full text |Cite
|
Sign up to set email alerts
|

Premature replacement of μ with α immunoglobulin chains impairs lymphopoiesis and mucosal homing but promotes plasma cell maturation

Abstract: Sequentially along B cell differentiation, the different classes of membrane Ig heavy chains associate with the Igα/Igβ heterodimer within the B cell receptor (BCR). Whether each Ig class conveys specific signals adapted to the corresponding differentiation stage remains debated. We investigated the impact of the forced expression of an IgA-class receptor throughout murine B cell differentiation by knocking in the human Cα Ig gene in place of the Sμ region. Despite expression of a functional BCR, homozygous mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 33 publications
3
60
0
1
Order By: Relevance
“…Instead, peritoneal cavity B-1 B cells were largely missing. These results are in accordance with, and extend, previous data (24) indicating that IgA can replace IgM to drive early B-cell development and instruct peripheral B-cell maturation. Whereas V H gene use may influence the FO versus MZ B-cell fate (27), our data reveal that BCR extrinsic factors critically contribute to this decision.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Instead, peritoneal cavity B-1 B cells were largely missing. These results are in accordance with, and extend, previous data (24) indicating that IgA can replace IgM to drive early B-cell development and instruct peripheral B-cell maturation. Whereas V H gene use may influence the FO versus MZ B-cell fate (27), our data reveal that BCR extrinsic factors critically contribute to this decision.…”
Section: Discussionsupporting
confidence: 82%
“…NT mice may result from impaired expression and/or signaling of a pre-BCR composed of an IgA H chain (24). Altered pre-BCR function may, in turn, prolong RAG-mediated recombination at the IgH locus, hence facilitating VH replacement.…”
Section: The Lower Number Of Pre-b Cells In V H Q52mentioning
confidence: 99%
“…Human IgA metabolism in this model mimics that of normal mouse IgA and notably features transport of pIgA from the internal milieu toward mucosal secretions. 15 Kidney dysfunction occurs in these mice when they additionally express the human FcaRI receptor. 16 We show that, by itself, the a1KI model mimics an initial phase of amorphous IgA deposition without inflammation following kinetics in which immune stimuli by environmental antigens modulate the IgA repertoire and structure.…”
Section: Discussionmentioning
confidence: 99%
“…15 We recently observed that IgA deposition occurs in these mice and leads to hematuria when deposits also include soluble CD89. 16 We now examined whether responses to environmental antigenic challenges induce modifications influencing initial IgA deposition and whether primary structures from different monoclonal IgA could also participate in this process.…”
mentioning
confidence: 99%
“…The absence of IgM expression in A150/A150 mice, together with previous findings that B cells expressing class-switched isotypes were poor competitors of IgM-expressing B cells in heterozygotes (28,29), led us to investigate the effect of the mutation on IgM expression. In the A150 model, this unfolds into three lines of inquiry: the effect of the mutation on IgM expression from the mutant allele, potential allelic inclusion, and allelic exclusion.…”
Section: Resultsmentioning
confidence: 99%